2021
DOI: 10.1021/acs.joc.1c00068
|View full text |Cite
|
Sign up to set email alerts
|

Stable Axially Chiral Isomers of Arylnaphthalene Lignan Glycosides with Antiviral Potential Discovered from Justicia procumbens

Abstract: Arylnaphthalene lignans (ANLs) were known to have axial chirality due to the biphenyl skeleton with hindered rotation at the single bond. However, the stable ANL atropisomers have not been isolated from nature until the present study. Phytochemical separation of the methanol extract of the stems and barks of Justicia procumbens led to the isolation of 11 ANL glycosides including four pairs of new atropisomers with stable confirmations at room temperature. Their structures were deduced from elucidation of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
(82 reference statements)
1
11
0
Order By: Relevance
“…Its molecular formula was determined to be C 27 H 26 O 13 by analysis of the HR‐ESI‐MS (559.1474 [M+H] + , calcd 559.1446) and NMR data (Table 1). The prominent UV absorption pattern at λ max 201, 255 and 309 nm and IR absorption bands at 3434 (hydroxy group), 1743 (ester group) and 1627 cm −1 (conjugated carbonyl group) of 1 were shown to be similar to those of the ANLs described in the literature [7,8] . Compound 1 was revealed to have the same ANL aglycone core structure containing a 6′‐hydroxy group by comparing its NMR spectral data (Table 1) with those of justatropmer A [7] …”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…Its molecular formula was determined to be C 27 H 26 O 13 by analysis of the HR‐ESI‐MS (559.1474 [M+H] + , calcd 559.1446) and NMR data (Table 1). The prominent UV absorption pattern at λ max 201, 255 and 309 nm and IR absorption bands at 3434 (hydroxy group), 1743 (ester group) and 1627 cm −1 (conjugated carbonyl group) of 1 were shown to be similar to those of the ANLs described in the literature [7,8] . Compound 1 was revealed to have the same ANL aglycone core structure containing a 6′‐hydroxy group by comparing its NMR spectral data (Table 1) with those of justatropmer A [7] …”
Section: Resultssupporting
confidence: 70%
“…Compound 3 was determined to have the molecular formula of C 29 H 28 O 13 based on the analysis of the HR‐ESI‐MS (565.1313 [M–CH 3 −CO+Na] + , calcd 565.1322) and NMR data (Table 2). The analysis of the 1D and 2D NMR spectral data revealed that 3 has a similar planar structure to the known ANL compound justicidinoside C [7] . Compound 3 differs from justicidinoside C only by the presence of an acetyloxy group substituted at C‐6′′ of the β ‐D‐glucose moiety in 3 , which were determined by the two extra carbon signals observed at δ C 20.78 and 172.62 in the 13 C NMR spectrum and the presence of the long‐range correlations from the methylene protons H 2 ‐6′′ [ δ H 4.237 (1H, dd, J =2.2, 11.9 Hz), 4.143 (1H, dd, J =6.9, 11.9 Hz)] and the methyl protons at δ H 2.086 to the carbon at δ C 172.62 in the HMBC spectrum (Figure 2).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations